2017
DOI: 10.1136/injuryprev-2016-042187
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the lower ignition propensity cigarettes standard in Estonia: time-series analysis

Abstract: This paper indicates that implementation of the LIP cigarettes standard has improved fire safety in Estonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Globally, several studies have indicated the positive impact of RFR cigarettes regulation on reducing cigarette-caused residential fires [9,11,34,35], and some studies concluded that implementation of fire-safe cigarettes is associated with reductions in residential fire mortality rates [10] and burns prevention [36]. On the other hand, some studies reported negative health impacts of RFR cigarettes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Globally, several studies have indicated the positive impact of RFR cigarettes regulation on reducing cigarette-caused residential fires [9,11,34,35], and some studies concluded that implementation of fire-safe cigarettes is associated with reductions in residential fire mortality rates [10] and burns prevention [36]. On the other hand, some studies reported negative health impacts of RFR cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, in many countries including Australia, reduced fire risk (RFR) cigarettes also known as fire safe cigarettes (FSC), lower ignition propensity (LIP) and reduced ignition propensity standard designs, were introduced to reduce the risk of smoking-related fires [9][10][11]. In 2010, Australia mandated that all cigarettes sold and imported meet the RFR regulation of 2008 and be self-extinguished [see Figure 1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations